Abnormality of the corpus callosum in coalmine gas explosion-related posttraumatic stress disorder. - Yang Zhang; Huabing Li; Xu Lang; Chuanjun Zhuo; Wen Qin; Quan Zhang (PLoS ONE, 2015)
Abnormal corpus callosum (CC) has been reported in childhood trauma-related posttraumatic stress disorder (PTSD); however, the nature of white matter (WM) integrity alterations in the CC of young adult-onset PTSD patients is unknown. In this study, 14 victims of a coal mine gas explosion with PTSD and 23 matched coal miners without experiencing the coal mine explosion were enrolled. The differences in fractional anisotropy (FA) within 7 sub-regions of the CC were compared between the two groups. Compared to the controls, PTSD coal miners exhibited significantly reduced FA values in the anterior sub-regions of the CC (P < 0.05, Bonferroni-corrected), which mainly interconnect the bilateral frontal cortices. Our findings indicated that the anterior part of the CC was more severely impaired than the posterior part in young adult-onset PTSD, which suggested the patterns of CC impairment may depend on the developmental stage of the structure when the PTSD occurs.